Impact of Pollution and Toxic Stress on Fish Health: Mechanisms, Consequences, and Mitigation Strategies - Satkar, Sagar Gorakh; Kumar , Anil; Anjana A.; Bhusare , Saiprasad; Sahu , Ashish; Gautam , Rohit Kumar (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Pollution poses a dire threat to fish health and aquatic ecosystems, permeating through various pathways and wreaking havoc on biological processes crucial for fish survival. Pollutants infiltrate fish through multiple routes, inducing direct toxicity and disrupting fundamental functions such as metabolism, hormonal regulation, and immune responses. These detrimental effects manifest in a plethora of consequences, including stunted growth, diminished energy reserves, heightened vulnerability to environmental stressors, reproductive impairments, increased susceptibility to diseases, and behavioral alterations that imperil their survival. To address this pressing crisis, proactive measures are indispensable, necessitating stringent regulations, the adoption of sustainable practices, and the enhancement of water treatment facilities to curtail the release of pollutants into aquatic environments. Simultaneously, reactive strategies must be deployed, focusing on remediation efforts to cleanse contaminated areas, facilitating the recovery of fish populations, and undertaking broader ecosystem restoration initiatives. Continuous research and vigilant monitoring play pivotal roles in discerning the nuanced impacts of pollution on fish health and gauging the efficacy of mitigation endeavors. Safeguarding fish populations is imperative for their well-being and preserving the health and equilibrium of the entire aquatic ecosystem, underscoring the urgency of concerted action to combat pollution's detrimental effects.